Peningkatan Literasi Digital Siswa SMP melalui Asesmen Berbantuan “GALAKSI” Terintegrasi Augmented Reality pada Materi Sistem Tata Surya - Bunga Lady Aliza; Fahmi Fatkhomi; Mobinta Kusuma; Bayu Widiyanto (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Digital literacy is a fundamental competency that junior high school students need to master. However, science assessment practices in schools are still largely conventional and have not been integrated with interactive digital media, limiting their potential to foster students' digital literacy. This study aimed to determine the improvement in students' digital literacy after the implementation of assessment assisted by the "GALAKSI" (Game Aktif Luar Angkasa Kuis Stacko Ilmu) media integrated with Augmented Reality in the Solar System topic. The study employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The research sample consisted of 32 seventh-grade students at SMP Negeri 1 Slawi, selected through purposive sampling. Data were collected using a digital literacy test on the Solar System topic and analyzed using the Paired Sample t-test and the N-Gain test. The results showed that the mean pretest score increased from 56.25 to 80.94 on the posttest. The Paired Sample t-test revealed a significance value of p < 0.001, indicating a statistically significant difference between the pretest and posttest scores. The N-Gain analysis produced a score of 0.59, which falls into the moderate category. Improvements were observed across all digital literacy indicators, with the highest increase found in the Problem Solving indicator. Therefore, assessment assisted by the "GALAKSI" media integrated with Augmented Reality was proven to effectively improve junior high school students' digital literacy in learning the Solar System topic.